OP0090 Mitochondrial dna mutations and respiratory chain dysfunction in lung fibrosis of systemic sclerosis. (12th June 2018) - Jaeger, V.K.; Lebrecht, D.; Nicholson, A.G.; Wells, A.U.; George, S.; Gazdhar, A.; Tamm, M.; Venhoff, N.; Geiser, T.; Walker, U.A.
Abstract : Background: Recent data have implemented reactive oxygen species (ROS) in the etiology of interstitial lung disease (ILD) in systemic sclerosis. Objectives: To investigate a role of large-scale somatically acquired mutations in mitochondrial DNA (mtDNA) and consecutive respiratory chain dysfunction as a trigger of ROS formation and lung fibrosis. Methods: Lung biopsies from patients with idiopathic interstitial pneumonitis and systemic sclerosis (n=31) were analysed for mitochondrial functions and compared with biopsies from 13 healthy controls (HC). From 17 patients we had simultaneous biopsies from the upper and lower lung. Results: Malondialdehyde as a marker of ROS formation was increased in ILD (p=0.007). The median proportion of mtDNA containing the pathogenic common deletion was 22.5% in ILD patients, compared to 0% in HC. This translated into a 3.8-fold diminishment of mtDNA-encoded cytochrome c-oxidase (COX2), but not nucleus-encoded (COX4) respiratory chain subunits in ILD compared to controls (p<0.0001) and a 33% diminishment of mtDNA-encoded cytochrome c-oxidase activity (p=0.001 vs controls). In all patients, the more fibrotic lower lungs had significantly more malondialdehyde (p=0.0004), mtDNA deletions (p=0.0006), and cytochrome c-oxidase dysfunction (p=0.0003) than the less-fibrotic upper lung counterparts. Conversely, lower lungs had significantly less (p=0.0003) mtDNA-encoded COX2 subunits in comparison to non-mtDNA-encoded COX4 subunits (figure 1). There was no association of any mitochondrial parameter with smoking status or age, and no difference between biopsies from patients with systemic sclerosis and non-specific interstitial pneumonitis. Conclusions: Our data support a role of mtDNA-mutations and consecutive respiratory chain dysfunction as a trigger and perpetuator of ROS formation in both, idiopathic interstitial pneumonitis and ILD of patients with systemic sclerosis. Disclosure of Interest: None declared